Conceptual model for methodological approaches to assessing the effectiveness of joint activities in the context of financial controlling (Economics and region, 2025)
It is established that financial controlling is a universal system of methods, tools and means of accumulating, processing and producing managerial and, above all, financial information on various aspects of functioning of individual business entities. Direct implementation of the financial controlling system in the process of joint economic activity between different entities is a prerequisite for improving the quality of management of such activity and contributes to the growth of efficiency of individual business entities. The article carries out a comprehensive structural and parametric analysis of the domestic practice of joint activity, allocates and substantiates advantages of its implementation, deepens methodical provisions of analysis of the financial controlling system and describes the process of formation and distribution of resources in the process of creation of joint activity. The essence of the mechanism of development of financial controlling of joint activity is substantiated with specification of its purpose, functions, tasks, definition and specification of the basic principles of implementation of such a mechanism, detailing of certain methods and instruments for enhancing the implementation of the financial controlling system in the work of joint ventures. The methodological ambushes of the functioning of such a mechanism have been lost by reinforcing the principles of its action, functional content, marking and specific target orientations of its implementation, methods and similar tools to ensure the active implementation of the financial control system in the work for the promotion of business activities.
Keywords: control; financial control; activity; corporate activity; corporate business; investment; foreign investment; comprehensive analysis; information security